Konsep Kebahagiaan Perpektif Syed Muhammad Naquib Al-Attas - Ridwan Atariq; Radea Yuli Ahmad Hambali (Gunung Djati Conference Series, 2023)
The purpose of the study is to analyze the Happiness Syed Muhammad Naquib al-Attas’s concept. The study uses a qualitative approach by positioning the researcher as a core instrument that then combined with the character's biographical approach. Then the littering study was used to collect data by excavating various relevant sources. In the study, it found that the concept of happiness Syed Muhammad Naquib al-Attas has almost in common with other sufi figures that has a differents with western concept about happiness. Syed Naquib al-Attas writes that a person's happiness does not only stop at the entity of the human body in life and also not only on an animal soul and mind. Happiness has a correlation with the exact principal truth and the purity of action in the process of achieving happiness itself.